2017
DOI: 10.15293/2226-3365.1705.14
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory responses of swimmers to hypoxia and hypercapnia

Abstract: Проблема и цель. Физиологические механизмы взаимодействия системы внешнего дыха-ния и сердечно-сосудистой системы при выполнении функции газообмена организма человека с участием хеморецепторов остаются недостаточно изученными. При этом можно полагать, что регулярные занятия конкретными видами спорта формируют специфические хемореактив-ные свойства кардиореспираторной системы. Целью работы было изучение хемореактивных свойств кардиореспираторной системы, а также росто-весовых данных и газообмена у пловцов разно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previously, researchers considered the features of the influence of hypercapnia on ventilation, using the concepts of threshold, response, reactivity, and sensitivity (slope). This approach has shown some specific ventilatory responses to hypercapnia and hypoxia possibly because of adaptation to frequent high-altitude climbing ( Puthon et al, 2016 ) or training-specific physiological adaptation ( Divert et al, 2017 ), genetic factors ( Goldberg et al, 2017 ), and even the presence of patent foramen ovale ( Davis et al, 2019 ). We have not found any differences in the considered respiratory parameters at rest, as well as ventilatory thresholds and CO 2 sensitivities before and after the high-altitude expedition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, researchers considered the features of the influence of hypercapnia on ventilation, using the concepts of threshold, response, reactivity, and sensitivity (slope). This approach has shown some specific ventilatory responses to hypercapnia and hypoxia possibly because of adaptation to frequent high-altitude climbing ( Puthon et al, 2016 ) or training-specific physiological adaptation ( Divert et al, 2017 ), genetic factors ( Goldberg et al, 2017 ), and even the presence of patent foramen ovale ( Davis et al, 2019 ). We have not found any differences in the considered respiratory parameters at rest, as well as ventilatory thresholds and CO 2 sensitivities before and after the high-altitude expedition.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that in swimming and skiing correlations between the responses of the cardiovascular and respiratory systems to acute hypoxic and hypercapnic tests are training-specific ( Divert et al, 2015 , 2017 ). Later we revealed that cardiorespiratory coherence changes in response to hypoxic exposure depend upon fitness status ( Uryumtsev et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the integrating factor for the respiratory and cardiovascular anatomical systems is the oxygen supply, acute hypoxia provides an appropriate paradigm within which to assess how the integration between systems changes across physical training. We have previously demonstrated that the magnitude of the relationship between the hypoxic responses of the systems depends on the kind of sport and the athlete’s qualification level ( Divert et al, 2015 , 2017 ). In contrast to less experienced swimmers, for example, high-level swimmers show high intra-group correlations between cardiorespiratory indices in response to acute hypoxia and hypercapnia ( Divert et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the magnitude of the relationship between the hypoxic responses of the systems depends on the kind of sport and the athlete’s qualification level ( Divert et al, 2015 , 2017 ). In contrast to less experienced swimmers, for example, high-level swimmers show high intra-group correlations between cardiorespiratory indices in response to acute hypoxia and hypercapnia ( Divert et al, 2017 ). Similarly, among ski racers, the highest results are achieved in the case of highly correlating chemoreflex responses of the respiratory and heart systems, assessed in hypoxic and hypercapnic tests ( Divert et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%